Meta Analysis: The Relationship between Hospital Management on Work Motivation among Nurse - Sunaryanti, Sri Sayekti Heni; Sunarno, Rita Dewi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: In terms of improving employee performance, hospitals must have efforts that aim to motivate employees to be disciplined and have a work spirit in doing their jobs, while the efforts that can be made are to implement good hospital management. Motivation will be formed if the management applied by the agency is good, so that self-improvement and service quality will run by itself. This study aimed to analyze the relationship between hospital management on work motivation among nurse.Subjects and Method: This study is a meta-analysis with PICO, population: nurse. Intervention: good hospital managemenet. Comparison: poor hospital management. Outcome: nurse work motivation. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “Hospital Management” OR “Hospital Care” AND “Nurse Motivation” OR “Work Motivation” or “Work Ambition” AND “Multivariate”. Articles included are full-text English from 2014 to 2019. Articles were selected using a PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 8 cross-sectional study articles from Asia (Indonesia, Malaysia, and Japan), Europe (Switzerland), Africa (Ghana), and North America (United States) were reviewed in the meta-analysis. Based on the results of the analysis, it was found that good hospital management can increase work motivation of nurses 1.91 times compared to poor hospital management (aOR= 1.91; 95% CI= 1.16 to 3.15; p= 0.01) and the results were statistically significant.Conclusion: Good hospital management increase nurse work motivation.Keywords: hospital management, work motivation, ambition, nurse.Correspondence:Sri Sayekti Heni Sunaryanti. Universitas Karya Husada Semarang. Jl. Kompol R. Soekanto 46, Semarang, Central Java. Email: ss.heni.s29@gmail.com. Mobile: +62 85216077830.Journal of Health Policy and Management (2022), 07(03): 185-192https://doi.org/10.26911/thejhpm.2022.07.03.02